Smart mobility – an analysis of potential customers' preference structures - Thomas Schulz; Markus Böhm; Heiko Gewald; Helmut Krcmar (Electronic Markets, 2020)
Cities around the world face major challenges caused by the extensive use of private cars. To counteract these problems, a new paradigm is necessary which promotes alternative mobility services. `Smart mobility' refers to a new mobility behaviour that makes use of innovative technical solutions, such as the IT-supported combination of different alternative mobility services during a trip from an origin to a destination. Unfortunately, relatively few customers use apps that provide recommendations for smart mobility and there is limited knowledge about the desires, priorities and needs of potential customers. To fill this gap, we use conjoint analysis to explore differences in smart mobility app preferences across groups of people with varying mobility behaviour. Our study also considers the effect of age and place of residence on preference structures. Our results show, for example, that only car drivers do not consider the price of the smart mobility app to be particularly important for their selection decision.
Keywords: C13; M310; R410; 620; Conjoint analysis; Mobility as a service (MaaS); Monetization; Preference structure; Smart mobility